If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x/3=x+4
We move all terms to the left:
2x/3-(x+4)=0
We get rid of parentheses
2x/3-x-4=0
We multiply all the terms by the denominator
2x-x*3-4*3=0
We add all the numbers together, and all the variables
2x-x*3-12=0
Wy multiply elements
2x-3x-12=0
We add all the numbers together, and all the variables
-1x-12=0
We move all terms containing x to the left, all other terms to the right
-x=12
x=12/-1
x=-12
| 25^2-150x=-225 | | 402x-2=2x+4 | | 5b-(2b+3)=3b+3 | | 109x-2=2x+4 | | 2n=43/5=9 | | 12d-11=-6-33d | | 3x-11x=-1 | | 3x/4x-4=4x+5/21 | | 5=3b+8b | | 1/4x-11=2-1/4= | | 4(x=2) | | 10x-4+5x=6+10x | | 5=4m-m+1 | | 8=32+8x | | 32=-1/2m | | 4x+11=7x+26 | | 10y+5=7y-10 | | 1/2m=32 | | S-1.8x=6.5 | | -8u+4(u-4)=-4 | | 2(a-4)=4a-(2a | | 5x+2(7x-11)=73 | | -256=-8(8+3n) | | X-0.2x=76 | | 56=-3x-4x | | 8b=25.6 | | 5x+2(7x-11)=-96 | | 4(y+5)-8y=y | | 14−23y=34−13y | | -11x-13=-46-11x= | | -144=8(6-3n) | | -3x+2=-15/4+3 |